Kinetics of graft copolymerization of acrylonitrile onto sago starch using free radicals initiated by ceric ammonium nitrate - Lutfor, M. R.; Rahman, M. Z. A.; Sidik, S.; Mansor, A. (Taylor and Francis, 2001)
This article reports an experimental investigation on the graft copolymerization of acrylonitrile monomer onto sago starch in which ceric ammonium nitrate was an initiator. The grafting reactions were initiated by the known free radical method. It was observed that the rate of graft polymerization and the grafting efficiency were dependent on the concentration of ceric ammonium nitrate (CAN), acrylonitrile (AN), sago starch (AGU, anhydro glucose unit), and the reaction period. The equation for the rate of polymerization (R p) is a first-order dependence of the monomer (AN) concentration and the square root of the CAN concentration. The experimental results were used to verify the kinetic equation relating the graft fraction of poly(acrylonitrile) on sago starch. © 2001 VSP 2001.